Analisis Kinerja Keuangan Perusahaan di Sektor Kesehatan yang terdaftar di Bursa Efek Indonesia - Fauziah Kumalasari; Munawarah Munawarah; Taufik Akbar Parluhutan (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2023)
The purpose of this study was to determine the financial performance of companies in the health sector listed on the Indonesia Stock Exchange. This study uses financial ratios, namely ROA, ROE, NPM and DER with a research period from 2019 to 2021. The research method used is descriptive quantitative by taking a sample of 17 companies engaged in the health sector both in selling medicines and providing health services. From the results of the study, it was found that PT. Industri Jamu dan Farmasi Sido Muncul Tbk. has good financial performance when compared to other companies. On the contrary, PT Sarana Meditama Metropolitan Tbk has a less good financial performance when viewed from the profitability ratio conducted in this study. In its financial statements, the company has not been able to record profits and is still experiencing losses from 2019 to 2021. In addition, there is also PT Indofarma Tbk. which has not been able to record profits in 2021 with the lowest profitability value of other companies.